Chapter 17 Family Constitutions and the Complexity of Family Businesses from a Counsel's Point of View - Lorenz Holler (Emerald Publishing Limited, 2023)
Family constitutions are relatively new to the law of family companies, although there might have been forerunners in the history of entrepreneur families. The practical importance and the proliferation of family constitutions in German family companies are increasing, along with the discussion of family constitutions in legal literature. This new instrument of family governance is not law driven but business driven, it has been designed by business advisors. Its analysis and classification are still at the very beginning in academic research and practice. Even though family constitutions are generally deemed to be without any legal effect and not legally binding, from a legal point of view, this assumption is at least highly questionable.
10.1108/978-1-83797-200-520231017; 10.1108/978-1-83797-200-520231017; Family Firms and Family Constitution; EBP099697173